Prompt Response, Cues-Pause-Point Therapies and Gender on Management of Echolalia among Children with Autism Spectrum Disorder - Jacob, Udeme Samuel; Adigwe, Gloria Oluchukwu; Pillay, Jace; Osisanya, Ayo; Olatunbosun, Stella Oluwakemi (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
The repetitive and delayed nature of echolalia can hinder the development of adaptive behaviors and impact the ability to establish rapport with others. This study investigated the effects of prompt response and cues-pause-point therapies on the management of echolalia among children with autism spectrum disorder. A pre-test, post-test, and control group of a 3x2 factorial matrix of quasi-experimental research design was used to assess the effect of the therapies on children with autism spectrum disorder in Ibadan, Nigeria. 90children with autism spectrum disorder were purposively selected using Diagnostic Statistical Manual- V (DSM-V) for ASD (0.70), Gilliam Autism Rating Scale/Third Edition (GARS-3) (in terms of sensitivity= 0.97, ROU/AUC= 0.93). In contrast, the Autism Treatment Evaluation Checklist (ATEC) (0.90) was used for the pretest and posttest to ascertain the presence of echolalia. Participants were assigned to one of three groups: prompt response, cues-pause-point therapies, or control (N = 90, male = 44, female = 46, age range = 3 –5 years old). Twenty-four prompt response and cues-pause-point therapy were held for each experimental group. The findings showed that the main effect of treatment (prompt response and cues-pause-point therapies) (F (2; 72) = 45.519, p<.05, ƞ2 = .558) on the management of echolalia among children with autism was significant, premised on this, the null hypothesis was rejected. The post hoc estimated marginal mean indicates that prompt response treatment was higher than cues-pause-point therapy; however, this difference was statistically significant. The study findings indicated that the impact of gender on managing echolalia in individuals with ASD was not statistically significant. Based on the findings, it is recommended that speech therapists, caregivers, and parents of children with autism spectrum disorder should seek alternative therapy that will take into cognizance other underlying factors associated with the presence of echolalia.